THE DATA SUBJECT’S RIGHTS AND LIABILITY FOR VIOLATIONS - Svetlov, Sergey (Administrative and Criminal Justice, 2018)
With the development of information technology, data processing tools for individuals are increasingly used in various areas of life. Their accessibility and simplicity in circulation lead to more and more mass application of technologies in the lives of individuals, organizations, and society. Personal data of individuals are subject to turnover, inevitably there is a need to protect the carriers of this data from using the information received against their rights and interests. Despite the urgency of the problem, the concept of the subject of protection does not have a clear definition, as a result, the participants in legal relations will seek to interpret it depending on their needs. The law determines the administrative responsibility for the violation of the processing of data of individuals, but does not provide for special mechanisms for compensation for the damage caused. Consequently, there is an urgent need to specify the norms related to the protection of these individuals.